THE IMPACT OF THE HERBICIDE GLYPHOSATE ON WATER SOURCES: A REVIEW - DRAGUS, Andreea; RISTOIU, Dumitru (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
Glyphosate is one of the most used herbicides worldwide. Its efficiency for weed control and cost make it a seemingly perfect choice in the agricultural area. Studies and monitoring reports show divergent results in what concerns the impact of glyphosate on water sources. Because of its nature the herbicide is prone to be found more in sediment and particulate matter than in water. Different compositions of the herbicide were found to pose certain negative impacts on species of amphibians, soil microbes and induce abnormalities in the activity of some enzymes in pregnant rats. In this review we will assess the literature in the last five years regarding this topic and portray the different findings.